(untitled) (Research, Society and Development, 2022)
Nursing technicians represent one of the largest numbers of health professionals and have a wide field of activity. The job market takes into account, in addition to technical skills, interpersonal skills in hiring professionals and training a professional with such a profile is a constant challenge. The objective was to describe the profile of the graduates of the technical course in nursing of the first ten years of existence of the researched institution, as well as the training received and insertion in the job market. This is a descriptive study with a cross-sectional design carried out with graduates of a technical course in nursing of the federal education network from 2010 to 2019. A structured instrument sent by Google Forms® was used. A total of 143 graduates were included, with a predominance of: women (93.7%, n = 134), young people (30.1 ± 8.6 years), entry into the labor market within one to six months after graduation (51 .5%, n = 67), working in hospitals (74.0%, n = 97), in critical sectors (26.7%, n = 37) and with low remuneration (average of R 1,702.92). The profile raised reinforces the professional characteristic of the majority of women, with a single employment relationship and low remuneration. The participants achieved rapid insertion in the job market and the education offered had a positive impact on their professional performance and on the achievement of their first job.